(untitled) (Scientia Agropecuaria, 2011)
The aim was to study the progress of the yellow spot, brown spot and leaf rust in wheat cultivar FUNDACEP 50 in Passo Fundo. Was evaluated the incidence of yellow spot [Drechslera tritici-repentis (Died) Drechs.] brown spot [Bipolaris sorokiniana (Sacc.)] and leaf rust [Puccinia triticina (Eriks)]. Values obtained were integralized as Area Under the Disease Incidence Progress Curve (AUDIPC) and to analyze the progress of the disease was considered the disease progress rate (r), which was obtained with the Logistic and Gompertz. Determination coefficients were high (0.93 to 0.98), as well as the mean square error (4.0706 to 7.6831). The r were 0.02 to 0.22 units, while the accumulated AUDIPC 787.5, 1216.3 and 1338.8 units for yellow spot, brown spot and leaf rust, respectively. The two models used satisfactorily explain the progress of yellow spot and brown spot, while the Gompertz explains better leaf rust.